DIMENSI KUALITAS PELAYANAN KESEHATAN GRATIS (JAMKESDA) PADA RUMAH SAKIT UMUM DAERAH DAYA KOTA MAKASSAR - Maryadi Maryadi (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2014)
This study aims to analyze the relationship and impact of service quality on free health patient satisfaction (jamkesda) using a model Sevqual (service quality), Reliability, Responsiveness, Assurance, Empathy and Tangible In Eastern Hospital of Makassar. The location of research is Power Makassar City Hospital, with quantitative research approaches and surveys. The study population was free jamkesda health patients who had received at least two times the service of outpatient and two times twenty- four hours on inpatient services. The sample used is a multi- stage random sampling of the number of patients jamkesda in 2012, a total of 25 339 patients as a basis to obtain samples using the formula slovin 0.75 percent to get a sample of 178 respondents. The instrument used was a questionnaire sheet Likerts scale models and to mendukungdata then used sheets obsevasi.Hasil questionnaire study showed that jamkesda patient characteristics, age, gender, education and employment do not have a relationship to the satisfaction of service, sedangkandimensi quality of service, (1) the dimensions of Reliability (Reliability), the medical officer has a relationship and kuntribusi a significant impact on service satisfaction. (2) Dimension Responsiveness (Responsiveness) owned by medical personnel Power Makassar City Hospital, have a significant effect relationship and contribution to the quality of services provided to patients jamkesda. (3) Warranty Dimensions (Assurance), the medical officer who has demonstrated the performance of services for serving patients jamkesda there is a relationship and a significant impact on the level of patient satisfaction jamkesda, (4) Dimensions of Empathy (Empathy), which is owned by each medical officer in giving jamkesda patient care have a relationship and kuntribusi significant influence on the quality of service. This shows empathy variables owned medical officer can provide jamkesda patient satisfaction. (5) The dimensions of physical evidence (Tangibles), the means and facilities for pre pasilitas Power Makassar City Hospital, and the relationship has a significant impact on the quality of patient care jamkesda. The higher kuntribusi dimensional quality, Reliability, Responsiveness, Assurance, Empathy and Tangible, the higher effect on the level of satisfaction of patient care provided in hospitals jamkesda Power Makassar.